Uptake of protective tetanus toxoid vaccine doses and maternal associated factors during pregnancy in armed conflict zone, hospital-based cross-sectional study - Kebede Bizuneh, Fassikaw; Muhidin Mustofa, Semira (Frontiers in Reproductive Health, 2024)
Background Vaccinating pregnant women with tetanus toxoid (TT) is crucial to prevent neonatal tetanus, reducing related deaths by 94%. In conflict zones with restricted access to deliveries, neonates face a fatality rate of 80%–100%. This study explores the uptake of protective TT vaccine doses and maternal associated factors during pregnancy in an armed conflict zone. Methods A hospital-based, descriptive, cross-sectional study was conducted of 357 pregnant women at delivery using simple random sampling. Data were collected through interviews with a structured questionnaire, and entered using Epi-data version 3.1, and exported using SPSS version 22 for further analysis. Binary and multivariable logistic regression analyses were used to identify significant variables for receiving protective TT doses during pregnancy at P < 0.05. Result In this study, 355 pregnant women were included, with response rate of 99.4%. The mean age of the participants was 27.65 ± 6.23 years. During the study period, 67.3% of pregnant women received a protective TT vaccine dose while 33.3% were missed due to escalated armed conflict. The dropout rates were significant from TT5 to TT2 (17.6%), TT5 to TT3 (11.9%), and TT5 to TT4 (6.1%). However, maternal associated factors for the uptake of the TT protective vaccine dose were identified, including being aged 36–49 years [adjusted odds ratio (AOR) = 3.7; 95% confidence interval (CI) 1.54–7.8; P = 0.001], completing high school (AOR = 3.05; 95% CI 1.5–8.9; P = 0.02), having an antenatal care follow-up (AOR = 9.4; 95% CI 2.9–24.3; P = 0.001), previous media exposure (AOR = 15.5; 95% CI 7.5–25.3; P = 0.001), and good maternal knowledge (AOR = 2.7; 95% CI 1.8–4.9; P = 0.02). Conclusion The uptake of the protective TT vaccine dose among pregnant women in a continued armed conflict area was low compared with previous study findings. Efforts should be made to increase vaccine uptake and reduce dropout rates by addressing both community and individual-level factors.